From Bullets to Banners and Back Again? The Ambivalent Role of Ex-combatants in Contested Land Deals in Sierra Leone. Issue 1 (April 2019) - Hennings, Anne
The rise of land deals poses unpredictable risks to war-torn societies, exposing them to the violent folds of the global economy. In Sierra Leone, commercial land leases have perpetuated the chieftaincy monopoly, further curtailed social mobility, and sparked particular resentment among youths and ex-combatants. Drawing on the concept of the "war machine, " I analyse how Kamajor militia fighters shape contestation against land deals and explore the attendant risks for remobilisation and conflict transformation. My findings, based on in-depth ethnographic field research, indicate that while aggrieved communities turn to Kamajor-run civil society organisations for support, Kamajor living in precarious conditions largely shy away from open contestation. While the historically close ties between the Kamajor and the chieftaincy have eroded in the wake of commercial land leases, complex patronage networks along with the moral setback encountered from the Special Court proceedings and tight surveillance thwart a more overt response. Yet, the Kamajor's background support remains key to the struggle of anti-plantation and mining activists.